Why so serious about foreign capital? - Ashish Kumar Sedai (International Journal of Financial Studies, 2019)
This study examines the cost and benefits of capital inflow in emerging economies and delineates equity and debt to examine the nature and trends of capital inflows in Brazil, Russia, India, China, South Africa (BRICS), East Asia and Sub-Saharan Africa since their economic reforms. We adopt a two-step process to address endogeneity and to tease out the causal effect of capital flow on economic growth and vice versa. First, we run the panel Granger causality test to examine the precedence of causality between per capita GDP growth, Foreign Direct Investment (FDI) inflows, portfolio inflows and the real effective exchange rate. We follow this test with a fixed-effect panel regression model to test for the magnitude of causality between the variables. The study finds the presence of a strong causality between FDI equity flows and a weak and lagged causality between short term capital flows and economic growth. In the short-run, there is bi-directional causality in growth and equity flows. In the longer run, the effects of equity fade away, but the effect of sustained debt kicks in. Among other results, an average currency appreciation for one-year causes equity inflow and causes GDP growth for two years.
Keywords: 330; BRICS; economic reforms; FDI; Granger causality test; panel Granger causality; portfolio